STRATEGI SURVIVAL KLINIK YOGA DARMA - Albert Yosua; Susilowati; Ni Luh Putu Eka Putri Andayani (Journal of Health Service Management, 2022)
Background: Yoga Darma Clinic, as a non-profit organization, is expected to survive in health services. There is a shift in revenue, where non-profit organizations are becoming more like for-profit organizations – becoming more professional and independent. The number of outpatient and inpatient visits has not reached the target, affecting the amount of income received by the clinic. The total operating expenses of the clinic are still greater than the income, so the Yoga Darma Clinic still receives subsidies from the foundation. Yoga Darma Clinic is expected to continue to exist in health services and be more independent in its operations. It takes innovation, adaptability to change, excellent service, and competitiveness. Therefore, an appropriate survival strategy is needed for the clinic to survive. Objective: To determine the right survival strategy for the clinic to survive. Methods: This research uses the type of research capstone project. The data were obtained through in-depth interviews with the purposive sampling method of sample selection. The data obtained from the interviews were triangulated by examining secondary data from observations and documentation. Results: This study found that the strength factors (strengths) had a score of 1.32 while the weaknesses (weaknesses) had a score of -1.02. The total IFAS score is 0.3. Furthermore, the opportunity factors (opportunities) have a score of 1.08, and the threat factors (threats) have a score of -1.20. The total EFAS score is -0.12. Conclusion: The SWOT analysis conducted by the researcher shows that the clinic is in quadrant II, meaning that the clinic must use a diversification strategy to maximize strengths and overcome existing threats.